TI_GERICHTE 12.2005.128 vom 17. August 2006 , simulazione - vendita di beni per sfavorire i creditori - costituto possessorio - TI Tribunale d'appello (2006)
simulazione - vendita di beni per sfavorire i creditori - costituto possessorio